Join the growing community of curious minds on IDNLearn.com and get the answers you need. Ask your questions and receive reliable and comprehensive answers from our dedicated community of professionals.
Answer:
[tex]g(x)=x^2-5x+4[/tex]
Step-by-step explanation:
We need to find a polynomial when subtracted from the polynomial [tex]3 x^2 +8-2x[/tex] yields a solution of [tex]2x^2 +3x+4[/tex]. Let it is g(x).
ATQ,
[tex]3 x^2 +8-2x-g(x)=2x^2 +3x+4\\\\3 x^2 +8-2x-(2x^2 +3x+4)=g(x)\\\\3 x^2 +8-2x-2x^2-3x-4=g(x)\\\\x^2-5x+4=g(x)[/tex]
So, [tex]x^2-5x+4[/tex] must be subtracted from the polynomial [tex]3 x^2 +8-2x[/tex] yields a solution of [tex]2x^2 +3x+4[/tex].